2013
DOI: 10.1590/s0103-84782013000200012
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography and photoacoustic spectroscopy for the assessment of soil greenhouse gases emissions

Abstract: Assessments of soil carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous oxide (N 2 O) emissions are critical for determination of the agricultural practices' potential to mitigate global warming. This study evaluated the photoacoustic spectroscopy (PAS) for the assessment of soil greenhouse gases (GHG) RESUMO As avaliações das emissões de dióxido de carbono (CO 2 ), metano (CH 4 ) e óxido nitroso (N 2 O) do solo são fundamentais para a determinação do potencial de práticas agrícolas em mitigar o aquecimento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
2
10
1
Order By: Relevance
“…The comparison of CO 2 and N 2 O emission rates measured by IRGA and PGA was very strongly correlated with GC measurements, an observation also reported by other authors (Pumpanen et al 2004;Iqbal et al 2013;Nicoloso et al 2013;Tirol-Padre et al 2014). In particular, the same trend was observed for both gas fluxes measured in the Cambisol and Haploxerert, which were characterized by different patterns of CO 2 and N 2 O emissions.…”
Section: Comparison Between Gas Flux Measurement Techniquessupporting
confidence: 88%
See 1 more Smart Citation
“…The comparison of CO 2 and N 2 O emission rates measured by IRGA and PGA was very strongly correlated with GC measurements, an observation also reported by other authors (Pumpanen et al 2004;Iqbal et al 2013;Nicoloso et al 2013;Tirol-Padre et al 2014). In particular, the same trend was observed for both gas fluxes measured in the Cambisol and Haploxerert, which were characterized by different patterns of CO 2 and N 2 O emissions.…”
Section: Comparison Between Gas Flux Measurement Techniquessupporting
confidence: 88%
“…Similar results to those observed in the present experiment were found for N 2 O fluxes by Iqbal et al (2013), who reported slightly higher emissions with PGA than with GC (+5%), However, by contrast, we did not find any difference in CO 2 flux measurements when comparing PGA and GC. Nicoloso et al (2013) observed an overestimation of 18.6 and 13.6% compared PGA to GC, for CO 2 and N 2 O, respectively; we did not find any differences between the techniques, which may have been due to the lower gas concentrations measured during our experiment. That also defined the positive effect of the compensation against water vapour and cross interference, the two main sources of interference on measurement, during the experiments.…”
Section: Comparison Between Gas Flux Measurement Techniquescontrasting
confidence: 52%
“…The syringes were stored in a cooler and analysed within 3 h after collection. The samples were injected in an INNOVA 1412 gas analyser (Lumasense Technologies, Denmark) where the content of CO 2 in the air samples was assessed by photoacoustic infrared spectroscopy (Yamulki and Jarvis, 1999;Nicoloso et al, 2013).…”
Section: Gas Sampling and Analysismentioning
confidence: 99%
“…Currently applied systems to monitor CO 2 concentrations from agricultural facilities include Photo Acoustic Spectroscope (PAS) Gas Analyzer [4,6,18,19,20,21,22,23,24,25]; and the Open-Path laser (OP-laser) [26,27,28,29,30]. The OP-laser and PAS analyzer have been extensively used by researchers seeking to monitor emissions from livestock barns in the last years, mostly mechanically ventilated.…”
Section: Introductionmentioning
confidence: 99%